Aristophanes and Solon’s laws - Ferreira Leão, Delfim (2015)
In the new edition of Solon’s Laws *D.F. Leão and P.J. Rhodes, The Laws of Solon. A New Edition with Introduction, Translation and Commentary (I.B. Tauris, London and New York, 2015)], the comedies of Aristophanes are for three times directly mentioned in connection with Solon (Av. 1353–7: Fr. 55a; Av. 1660–4: Fr. 50a; Nub. 1178–95: Fr. 123a), and two indirectly, through references in the scholia (ad Ar. Av. 1354: Fr. 85c; ad Ar. Eq. 658, Suda β 367: Fr. 64b). Despite this relative scarcity, those passages prove that Aristophanes was familiar with Solon’s laws, which he uses mainly for parodic purposes. The aim of this paper is to analyse those passages in their proper context and in comparison with passages from other authors, in order to discuss their validity as accurate sources for the study of Solon’s laws.